2013
DOI: 10.1007/s00586-013-2890-6
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index and risk of surgical site infection following spine surgery: a meta-analysis

Abstract: Purpose Inconsistent results have been reported in the literature on the association between obesity, expressed as increased body mass index (BMI), and risk for surgical site infection (SSI) following spine surgery. The objective of this study was to review and quantify the association between increased BMI and risk of spinal SSI in adults. Methods We performed a comprehensive search for relevant studies using PubMed, Embase, and references of published manuscripts. Study-specific risk measures were transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
59
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 70 publications
(80 reference statements)
4
59
2
2
Order By: Relevance
“…1,3,14,29 These findings may be attributable to patient positioning, soft-tissue dissection, and inefficient or absent specialized equipment to enable expedient surgical intervention. With respect to hospital stay, it is plausible that the higher prevalence of comorbid conditions seen in the obese group-for example, obstructive airway disease, hypertension, diabetes mellitus, and coronary artery disease-may complicate recovery and consequentially extend the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,14,29 These findings may be attributable to patient positioning, soft-tissue dissection, and inefficient or absent specialized equipment to enable expedient surgical intervention. With respect to hospital stay, it is plausible that the higher prevalence of comorbid conditions seen in the obese group-for example, obstructive airway disease, hypertension, diabetes mellitus, and coronary artery disease-may complicate recovery and consequentially extend the hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have described a strong association between BMI and SSI. 1,13,20,27 Interestingly, a handful of others have equally disagreed with this association. 15,22,30,32 Buerba et al 3 suggested that a BMI threshold ≥ 40 kg/m 2 may be more of a risk factor for SSI than all BMIs > 30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diyabetik yaralarda hipoksi ve hiperglisemi reaktif oksijen radikalleri antioksidan düzeyi aştığında serbest radikal salını-mıyla oksidatif strese neden olarak sürecin uzamasına ve biyofilm oluşumuna katkı sağlar (8,9). Kontrolsüz diyabette hiperglisemi, hücresel ve humoral immün yanıtı bozarak yarada hücresel disfonksiyona neden olur (10,11). Bakteriler tarafından "quorum sensing" (QS) sinyal molekülleri aracılığıyla üretilen virülans faktörleri polimorfonükleer lökositlerin fagositik aktivitesine karşı koruyucu rol oynar.…”
Section: Introductionunclassified
“…
The objective of this meta-analysis by Abdallah et al [1] was to synthesize evidence from studies that evaluated the association between body mass index and risk of surgical site infection following spine surgery. It is an interesting study.
…”
mentioning
confidence: 99%